Honey from stingless bees: a review on chemical parameters, content of bioactive compounds and their therapeutic properties (Research, Society and Development, 2022)
Honey is a food of high energy, functional and medicinal value produced mainly by African or also known as European bees, of the species Apis mellifera. However, there are other species of honey bees, which are known as stingless bees, popularized as native or indigenous bees. These are diversified into several species, which are divided into two groups, which can be from the Meliponini tribe and the Trigonini tribe. The honey of these bees is distinguished from the honey of African bees because it has a peculiar flavor and has a higher market value. Thus, the present study analyzed works published that best fit the topic addressed related to the chemical and functional characteristics of honeys from different species of native bees distributed throughout the Brazilian territory in order to contribute to the knowledge of their characteristics and potentials. In view of the studies, it was possible to observe the functional potential of honeys due to the presence of bioactive compounds, resulting in antioxidant, antimicrobial, anti-inflammatory, healing and immunological actions. It is worth mentioning the exclusivity of its composition, due to the variation and diversity of factors for the production of honey, such as botanical origin, meliponine species, climate, soil, humidity, among other factors that interfere in its composition. It is worth highlighting the need for more studies and research for a better understanding of the functional activities from honey and the importance of stingless bees for the scientific community, the environment, food production and the planet.